STK38 at the crossroad between autophagy and apoptosis. Issue 3 (3rd March 2016) - Joffre, Carine; Codogno, Patrice; Fanto, Manolis; Hergovich, Alexander; Camonis, Jacques
Abstract: We describe the STK38 protein kinase as a conserved regulator of autophagy. We discovered STK38 as a novel binding partner of Beclin1, a key regulator of autophagy. By combining molecular, cell biological and genetic approaches, we show that STK38 promotes autophagosome formation in human cells and in Drosophila . Furthermore, we also provide evidence demonstrating that STK38 with the small GTPase RalB, assist the co-ordination between autophagic and apoptotic events upon autophagy induction, hence proposing a role for STK38 in determining cellular fate in response to autophagic conditions.